1983
DOI: 10.1111/j.1469-8137.1983.tb03468.x
|View full text |Cite
|
Sign up to set email alerts
|

VANADIUM AS A TRACE ELEMENT IN THE BLUE‐GREEN ALGA, NOSTOC MUSCORUM: INFLUENCE ON NITROGENASE AND NITRATE REDUCTASE

Abstract: SUMMARYMolybdenum (Mo), a group VI B element (applied in the form of sodium molybdate at a concentration of 00177 ppm), is required for the nitrogenase and nitrate reductase activities of Sostoc muscorum and hence for growth on N, and NOj. These enzN-mic activities, as well as the growth of Mo-containing cultures, are significantly enhanced by the addition of 0-0125 ppm vanadium (V'), an element belonging to group V' (applied in the form of sodium vanadate). At concentrations above 00125 ppm, V addition inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Here, MA definitely serves as a metabolizable nitrogen source like NO 3 -rather than an energy source. This is substantiated by the finding that application of MA completely suppressed heterocyst differentiation and nitrogenase activity, as typically observed with NO 3 - (Table 3), exactly similar to the observations reported for the various sources of combined nitrogen (VAISHAMPAYAN 1983).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Here, MA definitely serves as a metabolizable nitrogen source like NO 3 -rather than an energy source. This is substantiated by the finding that application of MA completely suppressed heterocyst differentiation and nitrogenase activity, as typically observed with NO 3 - (Table 3), exactly similar to the observations reported for the various sources of combined nitrogen (VAISHAMPAYAN 1983).…”
Section: Resultssupporting
confidence: 75%
“…The liquid suspensions of the controls and treated samples were fragmented to individual cells by continuous one-hour gentle shaking with sterilized glass beads, after VAISHAMPAYAN (1983), which were inoculated in PETRI dishes in five replicates containing 1% agar medium (N combfree or 5 mM NO 3 -) H 3 mM glucose and/or 5 µM ATP. The inoculates were transferred to a growth chamber and showed colonial growth of the viable cells after two weeks of incubation.…”
Section: Determination Of Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that Mo serves as a constituent of the nitrate reductase and nitrogenase enzymes, participating in nitrate assimilation and N 2 fixation [337]. Likewise, V has been identified as essential nutrient influencing photosynthesis [338][339][340], cell division [341], and nitrogenase and nitrate reductase activities [342], as well as bromoperoxidase enzymes containing V at the active site [163,164]. The existing knowledge base about Mo and V mostly comes from research on freshwater green algae, blue-green algae [343,344], and some diatoms [340] because the major Mo species, MoO 4 2− , is known to be generally less available in seawater than in freshwater [345].…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…Mercury is a common pollutant and is most toxic in its organic form. In phytoplankton, Hg will bind to cytosolic ligands and distribute into the organelles [335] wherein it may affect photosynthesis [336][337][338] and increase reactive oxygen species inside the cell [339,340]. As a consequence of toxicity, phytoplankton has devised mechanisms to counter this toxicity, which includes the conversion of ionic mercury to elemental mercury [341].…”
Section: Mercury (Hg)mentioning
confidence: 99%